Chinese ideological and political teachers’ job satisfaction, loving pedagogy, and their professional success - Li, Yi; Wang, Xinpeng (Frontiers in Psychology, 2022)
Job satisfaction, loving pedagogy and teachers’ professional success, as three major emotional-psychological variables, have gradually gained its momentum in educational settings. The relationship among them has remained unknown. To address the existing gap, the current study set out to investigate the relationship among Chinese Ideological and Political (IAP) teachers’ job satisfaction, loving pedagogy, and their professional success. To carry out the study, 1189 Chinese IAP teachers with different majors, various academic degrees, and diversified teaching experiences voluntarily took part in the present study. The results of the study showed that job satisfaction and loving pedagogy could jointly predict 46.8 of the variance of teachers’ professional success. Both variables were the significant predictors of professional success, while loving pedagogy was a better predictor, solely explaining 39.4 of teacher success’s variance. Based on the findings, some pedagogical implications for educational institutions, administrators, and IAP teachers were discussed in the article. Future research directions and limitations were also mentioned.